CPW-Fed Fractal Monopole Antenna for UWB Communication Applications - Zehforoosh, Y.; Naser-Moghadasi, M. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This paper presents the results of a novel fractal monopole antenna that exhibits UltraWideband (UWB) performance. Higher order iteration of the fractal motif constituting the antenna was analyzed and its performance evaluated in order to optimize the antenna’s characteristics. Compared to a typical circular monopole antenna, the proposed antenna generates reflection-coefficient resonances that significantly improve its impedance bandwidth by 160%. The antenna’s measured performance conforms to the desired UWB specifications.